Impact of Sanctions of European Union and Unites States of America on the Development of Russian Oil and Gaz Complex - Nikulina, Anni Yulievna; Kruk, Marina Nikolaevna (International Journal of Economics and Financial Issues, 2016)
The present article analyzes the impact of the restrictive measures adopted by the European Union (EU) and the United States of America (USA) against Russian Federation. In particular, the item aims to analyze the sectoral sanctions in oil and gas industry. Sanctions in oil and gas sector are extended to the supply of equipment particularly to the technologies for development of the Arctic shelf. The article proposes and analyzes scenarios of Russian oil and gas complex in the conditions of restrictive measures from the part of Western countries. As for equipment authors offer two options: the importation of equipment through third countries or copying it from Western equipment. In the area of finance they offer attracting Asian credits and the use of the National Welfare Fund of Russian Federation. Keywords: oil, gas, sanctions, Arctic, offshore JEL Classification: F510